METHOD FOR PRECISE LANDING OF UNMANNED AERIAL VEHICLE - Jamolova , Gulbanbegim Muzaffar qizi; Bo‘riyev , Sardor Norovich; Tursunov , Akhmadjon (Educational Research in Universal Sciences, 2023)
An aircraft landing is a very challenging problem. Due to the risks involved, pilots practice touchdowns for a long time during the landing phase. Over the past ten years, research on the development of autonomous landing technologies has been vigorous. This article gives a general overview of landing procedures, covering everything from vision-based landings to GPS-based ones, and basic controls to sophisticated ones. It aims to give a comprehensive overview of the landing control problem’s current state and controller design. The comparison presented in this paper is based on factors including vehicle type, problem design assumptions, methodological approaches, and algorithm performance in real-world scenarios.